2015
DOI: 10.3906/sag-1306-116
|View full text |Cite
|
Sign up to set email alerts
|

Salivary glucose and antioxidant defense markers in type II diabetes mellitus

Abstract: Background/aim: To evaluate salivary antioxidant defense markers, their correlation with salivary glucose, and glycemic status in type II diabetes mellitus (DM). Materials and methods:The study included 53 diabetic patients and 40 healthy subjects. Salivary glucose, blood glucose, and uric acid (UA) were determined by specific enzymatic methods. Total antioxidant activity (AOA), glutathione (GSH), catalase (CAT), superoxide dismutase (SOD), and total protein were determined spectrophotometrically.Results: Sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…Type 2 diabetics had significantly higher USWG/RCBG levels than the controls, a fact which has been documented in previous studies. [513141516171819] The correlation between RCBG and UWSG could plausibly be because of leakage of glucose from blood across the basement membrane of salivary glands. Microvascular alterations in the blood vessels that are commonly seen in type 2 diabetics could also contribute to increased salivary glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetics had significantly higher USWG/RCBG levels than the controls, a fact which has been documented in previous studies. [513141516171819] The correlation between RCBG and UWSG could plausibly be because of leakage of glucose from blood across the basement membrane of salivary glands. Microvascular alterations in the blood vessels that are commonly seen in type 2 diabetics could also contribute to increased salivary glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in salivary glucose (SGlc) beyond the normal levels in Type 2 DM has been reported by many investigators ( 68 ). However there are also contradicting reports where decreased SGlc levels in DM as compared to the controls was observed ( 69 ).…”
Section: Disorder Specific Salivary Biochemical Variationsmentioning
confidence: 93%
“…In this study salivary TAC level was lower in T2DM patients with VD risk compared to T2DM patients without VD risk. In a recent study conducted by Mussavira et al (20) , TAC was decreased in the saliva of T2DM patients in comparison with healthy controls. In regard to TAC level in patients with CVD, several studies had found a significantly lower serum TAC level in patients with CVD (21,22) .…”
Section: Discussionmentioning
confidence: 82%
“…Saliva has a dynamic diagnostic properties aiding in the detection of oral and systemic disease by using the salivary biomarkers (7,8) . The relationship of salivary oxidative stress markers including: TBARS, UA and TAC were studied in relation to T2DM in previous studies (9,10) . In this study the aim is to investigate the risk of VD in T2DM patients through studying salivary TBARS, UA and TAC all together as an indicator of risk for VD.…”
Section: Introductionmentioning
confidence: 99%